Longitudinal predictors of problematic alcohol use in adolescence: a 2-year follow-up study - Wartberg, Lutz; Fischer-Waldschmidt, Gloria; Kriston, Levente; Hoven, Christina W.; Sarchiapone, Marco; Carli, Vladimir; Wasserman, Danuta; Resch, Franz; Brunner, Romuald; Kaess, Michael (Addictive behaviors, 2021)
Alcohol consumption in adolescence is widespread. Several studies have investigated alcohol use in minors and its consequences in adulthood, but prospective findings on psychosocial predictors for problematic alcohol use (PAU) already in youth are still limited. Next to genetic aspects, psychosocial predictors appear to be particularly relevant. The objective of the present longitudinal survey was to explore psychosocial influences on PAU in adolescence. At baseline, 1,444 adolescents (52.1% girls, average age: 14.65 years) were surveyed. Two years later (at follow-up), we were able to re-assess 515 adolescents (mean age: 16.60 years). Both times, a standardized questionnaire was applied to explore PAU and various psychosocial aspects. We conducted multiple imputation, created 100 datasets with a Markov Chain Monte Carlo algorithm and calculated regression analyses to identify predictors for PAU. In a multivariable analysis, we found that female gender (protective factor), school-type ‘Gymnasium’ (highest level of school education, protective factor), PAU, more conduct problems and lower psychological well-being (all at baseline) predicted adolescent PAU at follow-up. In supplementary analyses for frequent alcohol use (regardless of quantity) and high alcohol consumption quantity (regardless of frequency), these predictors could only partially be found again. According to the findings of the present study, psychosocial aspects are relevant for PAU in adolescence, and particularly psychological well-being should be given more attention in primary prevention measures and treatment approaches.